Fostering Effective Learning Environments: Educator Approaches to Applying Reading, Writing, and Speaking Ethics - Ahmad Faroji; Ilzamudin Ma'mur; Anis Zohriah (International Journal of Science Education and Cultural Studies, 2024)
This study examines the roles of teachers in creating a positive and supportive learning environment, with a focus on the application of ethics in reading, writing, and speaking. The research method is literature studies, and the data sources are taken from a variety of articles in relevant scientific journals and books. The research phases begin with the formulation of goals, searching and gathering relevant references, identifying and classifying various references, and, finally, analyzing the results of the research. The study's findings demonstrate the critical role that teachers play in establishing a productive learning environment, particularly when it comes to incorporating the ethics of speaking, writing, and reading into routine instruction. Teachers can support students in developing good communication skills and strong moral foundations by raising awareness of ethical ideals and helping students apply these ideas in their daily lives. According to these studies, creating a learning atmosphere that values justice, honesty, and tolerance for other viewpoints can help students learn more effectively.